Best books for junior high readers - Gillespie, John Thomas, 1928- (New Providence, N.J. : R.R. Bowker, 1991)
Annotated list of some 6000 best books for young teens. Includes curriculum based titles as well as recreational reading.
Includes bibliographical references and indexes.
Booklist.
Wilson's Junior High School.
Professional
Keywords: Best books -- United States; Children's literature -- Biography; Junior high school libraries -- United States -- Book lists; Junior high school students -- United States -- Books and reading; Best books; Children's literature -- Bibliography; High school students -- Books and reading; Junior high school students -- Books and reading